RELEVANSI INERANSI KITAB YOEL 2:28-32 TERHADAP NUBUATAN MASA KINI - Tony Suhartono; Kasten Situmorang; Hendry Sitohang (JURNAL TABGHA, 2022)
The purpose of this study is to explain the importance of the inerrancy of the Bible from the author's point of view, prove that the fulfillment of the prophecy of Joel 2:28-32 and find out the relevance of the gift of prophecy today with qualitative descriptive research methods, where data collection techniques are by means of literature study and testimony. Writer. The findings and conclusions (1) that the inerrancy of the Bible is very important to be studied by believers, because it has implications for all areas of life. (2) The prophecy of the book of Joel 2:28-32 began to be fulfilled at Pentecost when the disciples received the outpouring of the Holy Spirit and will end until the perfect one comes the second time, namely Jesus Christ the Lord. (3) The Bible never states that prophecy ends, if the Lord Jesus has not come a second time. So the author concludes that prophecy still exists today and is very much needed in building and maturing God's congregation. Keywords: Inerrancy, Prophecy, Present